ANALISIS PENYULUHAN DAN KEBERDAYAAN PETANI KARET POLA SWADAYA DI KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Sergius Septian Sianturi; Roza Yulida; Eri Sayamar (Indonesian Journal of Agricultural Economics, 2016)
The purpose of this research are: (1) To describe the role of extension on independent small holder farmers of rubber; (2) To describe empowerment level of the farmers; (3) To describe the aims of extension; (4) To analyze influence the role’s of extension toward empowerment; (5) To analyze influence the empowerment toward the aims of extension. This research was conducted at Pujud Village and Suka Jadi Village in Pujud Sub District Rokan Hilir District. Research’s respondent was determined by key informan sampling methods with number of respondent were 120. The consideration to choose the location is the location that has active extension activities and has farmer group. Validity, reliability, outliers, normality, singularity and multicolinearity analysis has been done on the measuring instruments. To answer the first, second, and third purpose of this research using likert’s scale summated rating (SLR). To answer the fourth and fifth research purpose was using structural equation modeling (SEM) with the AMOS program. The result shows (1) The role of extension has shown quite on independent small holder farmers activity; (2) The empowerment level of farmers on the categorize quite with the extension activities as seen from empowerment human resource, productive economy, and the farmers institutional; (3) The aims of extension has been reached as seen from better farming, better business and better living; (4) the role of extension has proven directly influence significantly toward level of farmer’s empowerment; (5) the level of farmer’s empowerment has proven directly influence significantly toward reach of the role extension aims.